Pengaruh Penggunaan Dompet Digital Dana Terhadap Perilaku Konsumtif Pada Mahasiswa Universitas HKBP Nommensen Medan - Sagala, Rista Suci Kristiani; Sihombing, Natalia E.; Pasaribu, Vera A.R. (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to determine the effect of using digital wallets on consumer behavior among students at HKBP Nommensen University, Medan. This research uses a quantitative approach with non-probability sampling techniques. The two variables examined in this research are digital wallet funds (Independent Variable) and consumptive behavior (Dependent Variable). The data collection technique used in this research used a questionnaire distributed to 98 students at HKBP Nommensen University in Medan. Based on hypothesis testing with the t test, the tcount for the digital funds wallet variable is 7.331, where this value is > from t table of 1.661 with a significant value for the digital funds wallet variable being 0.000 < the significance level of 0.05 (5%). So it can be concluded that digital fund wallets have a positive and significant effect on consumer behavior.